Industry 4.0 Maturity Model for Manufacturing Small- and Medium-sized Enterprises - Simetinger, František (2023)
Industry 4.0 is an emerging topic with growing importance. This dissertation thesis and related research describe the process of critical factors’ identification relevant to small- and medium-sized enterprises during the implementation of Industry 4.0 principles. This thesis’s primary goal is to create a new Industry 4.0 maturity model that reflects these critical factors and provides a usable form for these organizations. At the same time, this new Industry 4.0 model adopts the best practices from the existing Industry 4.0 maturity models. The Theoretical Part of this thesis involves literature research, comparative analysis of existing Industry 4.0 maturity and readiness models, and complementary research. Literature research focused on Industry 4.0 in combination with comparative analysis resulted in the identification of critical elements but also gaps in the analyzed models. The following complementary research has resolved these gaps and has proposed solutions for them. Together, these findings represent key inputs for the creation of the new Industry 4.0 Maturity Model for Manufacturing Small- and Medium-sized Enterprises, abbreviated and referred to as I4MMSME. The following part, Creation and Description of I4MMSME, describes the model creation process. I4MMSME utilizes inputs from the Theoretical Part. This part also describes I4MMSME itself with all critical assumptions, traits, and elements. The next two parts, Survey and Model Evaluation, describe the survey process between chosen manufacturing enterprises and evaluation of I4MMSME. The survey conducts an assessment of chosen manufacturing enterprises. The evaluation was performed via case studies where the development of two manufacturing enterprises is described from I4MMSME's perspective, a comparison of an assessment model from the European Union, and a brief summary of feedback in other publications. The last part, Conclusions, summarizes the research and its main benefits.